The Mitochondrial Interplay of Ubiquinol and Nitric Oxide in Endotoxemia - Lisdero, Constanza L. (2004)
This chapter focuses on role of ubiquinol (UQ) and nitric oxide in endotoxemia. UQ is endogenously synthesized in every organ in a specific pathway branched from cholesterol biosynthesis. Organs have different ubiquinol content depending on the activity of the biosynthetic pathway. In addition to its role as electron carrier in the mitochondrial respiratory chain, UQ exhibits prooxidant and antioxidant properties. The chapter provides the methodological bases that support the relation between UQ content, mitochondrial NO steady-state concentration, and peroxynitrite-mediated mitochondrial damage in representative organs. The chapter also focuses on the contribution of mtNOS to peroxynitrite formation in mitochondria. The chapter presents an experimental model, elaborating endotoxemic animals and sample preparation, and homogenate and mitochondrial preparations. Sources of NO in endotoxemia are also analyzed in the chapter. The chapter discusses the measurement of NOS expression and activity and analyzes the role of ubiquinol in endotoxemia. The endotoxemic mitochondrial damage is also analyzed in the chapter. The chapter elaborates the ubiquinone content and NO-induced hydrogen peroxide production by mitochondria..